Education Model for Children with Special Needs in Ainul Yakin Islamic Boarding Schools Gunung Kidul, Yogyakarta - Muntakhib, Ahmad; Taruna, Mulyani Mudis; Wahab, Wahab (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2023)
Children with special needs require special treatment in developing their potential, but parents and educational institutions, including Islamic boarding schools, are not aware of it. This special treatment requires an educational model that can provide comprehensive services to children with special needs. Therefore, the educational model applied by educational institutions will determine the success of education. The accuracy of parents and Islamic boarding schools in understanding children, especially children with special needs, is the main key in determining  curriculum and educational model developed. One of the Islamic boarding schools that maintains and develops the potential of children with special needs is the Ainul Yakin Islamic Boarding School. This boarding school tries to develop the potentials of children with special needs appropriately and efficiently. This paper seeks to reveal and understand why the Ainul Yakin Islamic boarding school manages students from children with special needs?, How does Islamic boarding school classify students from children with special needs? This research is a qualitative research with a case study approach. Collecting research data by means of documentation, observation, and in-depth interviews. The research data were analyzed using the Miles and Hubberman model. This study shows that the Ainul Yakin Islamic boarding school views children with special needs as special pearls and. Second, Islamic boarding schools classify students into three groups, namely independent students, assisted students, and self-help students. Third, the education model in Islamic boarding schools is a practical-applicative education model, namely by students, from students and for students with the main activity is prayer.